2018
DOI: 10.3851/imp3159
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength is Impaired in Men but not in Women Living with HIV Taking Antiretroviral Therapy

Abstract: HIV infection is associated with impaired dynamic and isokinetic strength in men compared to HIV-uninfected controls, but not in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…17 This information is relevant, since this problem is a predictor of functionality. The loss of muscle mass would be the probable contributing factor for this finding, 18 agreeing with the publication by Lédo et al 16 Oliveira et al 19 demonstrated in one study that HIV infection is associated with decreased muscle strength in men when compared to groups of non-HIV infected controls. However, this lower muscle strength observed in men was not associated with a decrease in muscle mass.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…17 This information is relevant, since this problem is a predictor of functionality. The loss of muscle mass would be the probable contributing factor for this finding, 18 agreeing with the publication by Lédo et al 16 Oliveira et al 19 demonstrated in one study that HIV infection is associated with decreased muscle strength in men when compared to groups of non-HIV infected controls. However, this lower muscle strength observed in men was not associated with a decrease in muscle mass.…”
Section: Discussionsupporting
confidence: 80%
“…21,22 The physical consequences of HIV involve metabolic, neurological and structural, and inflammatory muscular abnormalities. 19 In addition, the use of ART has been associated with mitochondrial dysfunction and motor impairment. 23 In the present study, of the 71 individuals (41.27%) who used ART, 15.5% presented dynapenia, corroborating with findings in the literature, what associates clinical symptoms such as myalgia and muscle weakness after the use ART.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, levels of insulin and inflammation were stronger predictors of CRF in our sample rather than other variables, such as BMI. Others have also suggested that PLWH are predisposed to lower levels of physical fitness through cardiovascular mechanisms (i.e., presence of hypertension), rather than others (i.e., amount of lean body mass; Oliveira, Wiechmann, Narciso, Webel, & Deminice, 2018; Oursler et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our findings, Yarasheski et al [55] reported lower muscle mass in men but higher muscle mass among women living with HIV compared with controls, after multivariable adjustment. Also, Oliveira et al [26] found impaired dynamic and isokinetic strength in men living with HIV, but not in women, compared with uninfected controls. One mechanism of this effect may be from greater body fat in women: studies on AIDS wasting disease observed that greater adipose tissue may protect against subsequent loss of muscle mass [56,57].…”
Section: Traditional and Hiv-related Risk Factors Contribute To The Dmentioning
confidence: 97%
“…In this review, we selected original sarcopenia studies which adopted one of the above-mentioned sarcopenia operational definitions. We are aware that there are a large body of literature that has assessed and described the characteristics of muscle mass or function in PLHIV, variables which were usually impaired compared with people without HIV [7,26,27]. But because these variables have been assessed separately, or studies did not employ a cut point to classify subjects with low or normal range, these studies were not included in this review.…”
Section: Sarcopenia Definitionmentioning
confidence: 99%